The ordinary virtues: moral order in a divided world - Ignatieff, Michael (Harvard University Press, 2017)
This is a study of what ethical principles and practices people around the world hold in common and what institutions best allow virtue to flourish. It is based on a Carnegie Council project on comparative ethics that Michael Ignatieff has run for the past three years. Most works of comparative ethics look at formal systems of belief. What, for example, do Christian and Confucian texts say about the role of the family? What do the Koran or John Rawls say about treatment of the poor? This is, by contrast, a work of "lived ethics." Ignatieff took a team of researchers around the world to examine what values and ethical beliefs guide diverse people in practice. They went to places where people are living under unusual stresses or where contemporary social challenges are particularly clear. They went to Brazil, for example, to discuss life where corruption is a serious problem, to Sarajevo to talk about reconciliation, to Queens in New York to talk about diversity, and to Fukushima, Japan, to talk about disaster and recovery. Overall, they found more commonality than they were expecting, that whatever formal systems of belief prevail, people tend to orient themselves in similar ways around the values of trust, tolerance, forgiveness, reconciliation, and resilience. But where people are suffering they often doubt that others share their ethical beliefs and begin to circle the wagons to defend their own group. We shouldn't expect citizens to be heroes. So what institutions and political arrangements encourage or inhibit virtue? Overall, Ignatieff says, liberal constitutionalism seems most effective, but only as long as poverty and inequality are not allowed to get out of hand.--